Increase Optimism of Adolescents Who Experience Nonsuicidal Self-Injury Through Mandala Drawing Activities - Arifa, Dinsya; Nofriza, Fatma; Fitniwilis, Fitniwilis (Universitas Mathla'ul Anwar Banten, 2023)
Adolescence is one of the phases with a fairly fluctuating dynamic level of optimism. Adolescents with low levels of optimism are prone to feeling hopeless to hurt themselves. The tendency of adolescents to hurt themselves into a condition called Non-Suicidal Self-Injury (NSSI). An alternative immediate treatment of the condition of students experiencing NSSI with low levels of optimism was tested in this study. Testing using the Pre-Experiment method with the types of One Group Pre Test and Post Test with subjects as many as ten adolescents selected based on purposive sampling technique. The alternative treatment used is the drawing mandala activity which is a drawing pattern used as a medium for channeling emotions. The analysis used in this study is a test that compares two conditions, namely the Paired Sample T-test. The results of the analysis conducted show that Mandala drawing activities can increase the level of optimism of adolescents who experience NSSI. So that Mandala activities can be used as a medium for immediate handling for NSSI teenagers who have low optimism. However, the results of this study need to be tested further in a wider population and also with generalizable methods.